2020
DOI: 10.1098/rstb.2019.0139
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysiologies of Jurassic marine crocodylomorphs inferred from the oxygen isotope composition of their tooth apatite

Abstract: Teleosauridae and Metriorhynchidae were thalattosuchian crocodylomorph clades that secondarily adapted to marine life and coexisted during the Middle to Late Jurassic. While teleosaurid diversity collapsed at the end of the Jurassic, most likely as a result of a global cooling of the oceans and associated marine regressions, metriorhynchid diversity was largely unaffected, although the fossil record of Thalattosuchia is poor in the Cretaceous. In order to investigate the possible differences in thermophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 88 publications
2
34
0
Order By: Relevance
“…A previous analysis of the thermophysiology of marine reptiles showed that Plesiosauria, Ichthyosauria and (probably) Mosasauridae were endotherms [31]. Results obtained by Séon et al [8] for Thalattoshuchia (marine crocodylomorphs) are consistent with hydroxyapatite formed under temperatures intermediate between those of ectotherms and endotherms, and behavioural adjustments are speculated to have played a role in their thermoregulation.…”
Section: Thermometabolismmentioning
confidence: 71%
See 1 more Smart Citation
“…A previous analysis of the thermophysiology of marine reptiles showed that Plesiosauria, Ichthyosauria and (probably) Mosasauridae were endotherms [31]. Results obtained by Séon et al [8] for Thalattoshuchia (marine crocodylomorphs) are consistent with hydroxyapatite formed under temperatures intermediate between those of ectotherms and endotherms, and behavioural adjustments are speculated to have played a role in their thermoregulation.…”
Section: Thermometabolismmentioning
confidence: 71%
“…'Vertebrate palaeophysiology' will promote a better understanding of how organism-environment interactions have evolved in terms of energy budgets, predator-prey relationships and sensitivity to environmental change. The research areas covered by this theme issue include: phospho-calcic metabolism [2], acid-base homeostasis [3,4], thermometabolism [4][5][6][7][8][9], respiratory physiology [10], skeletal growth [11], palaeopathophysiology [12,13], genome size and metabolic rate [14], and a concluding historical perspective [15]. Sometimes, the two components ( physiological mechanism and palaeobiological inference) are proposed in separate papers (for instance, three contributions devoted to mechanisms of thermogenesis mechanisms [5][6][7] and three papers dealing with the thermometabolic inferences in extinct taxa [4,8,9]).…”
Section: Introductionmentioning
confidence: 99%
“…The basal cetaceans that we consider most skeletally analogous to semiaquatic thalattosuchians-the nearshore remingtonocetids, which had teleosauroidlike elongate snouts, comparatively long necks, forelimbs and hindlimbs used in swimming, and robust pelves (1, 33)-had miniaturized pelagic-style labyrinths, and flourished for only a few million years. It may be that cetaceans were able to adapt more quickly to fully pelagic lifestyles, because they evolved from terrestrial ancestors that were already endothermic and gave live birth, whereas metriorhynchids had to develop these attributes after entering the water (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Fraas, 1902;von Arthaber, 1906;Andrews, 1913;Fernández & Gasparini, 2000Young et al, 2010;Herrera et al, 2013aHerrera et al, , 2013bSachs et al, 2019a;Schwab et al, 2020). It has also been suggested that metriorhynchids evolved a non-homeothermic mode of endothermy and were viviparous (see Herrera et al, 2015a;Séon et al, 2020).…”
Section: Take Down Policymentioning
confidence: 99%